Hohokam Canal Irrigation and the Formation of Irragric Anthrosols in the Middle Gila River Valley, Arizona, USA. Issue 4 (July 2015) - Woodson, M. Kyle; Sandor, Jonathan A.; Strawhacker, Colleen; Miles, Wesley D.
<x xml:space="preserve">Abstract</x> Irragric anthrosols form as a result of prolonged deposition of fine sediments from irrigation water. Ancient irragric soils centuries to millennia old occur in several world regions, especially in arid environments of Asia and the Americas. This article presents evidence for an ancient irragric anthrosol in the North American Southwest, along the Snaketown Canal System in the Middle Gila River Valley, Arizona. This pedostratigraphic unit was formed as a result of a millennium of irrigation by Hohokam farmers from A.D. 450 to 1450. The irragric soil consists of a mantle of silty‐to‐loamy textures with minimal soil formation overlying a natural argillic horizon on a Pleistocene stream terrace. A soil mapped independently by the United States Department of Agriculture‐Natural Resources Conservation Service with these horizons corresponds closely with the canal system. Soil within the canal system tends to be lower in salt, sodium, and pH compared with external soils. This suggests that the irragric process improved soil for crop production through long‐term leaching and additions of fresh sediments with the irrigation water. This anthropogenic process of canal sedimentation has had a long‐lasting impact on the sedimentary record and soils in this arid environment.